Safety data sheets as an information pathway on hazards of occupationally used cleaning agents - Erfani, Behnaz; Vilela, Libe; Julander, Anneli; Schenk, Linda (Regulatory toxicology and pharmacology, 2023)
To investigate consistency and accessibility of asthma and skin allergy hazard information in safety data sheets (SDSs) for cleaning agents on the Swedish market, we compiled a database of 504 SDSs and 351 therein declared ingredients. Labelling of products was compared to that of ingredients according to harmonised classification. For each ingredient, also notified classification and three additional sources on sensitising properties were compared. Product labelling most frequently indicated corrosion and irritation hazards. Only 3% of products were labelled as skin sensitisers and none as asthmagens. According to harmonised classification, 9% of products contained skin sensitisers, using other information sources increased the number to 46%. While 2% of products contained respiratory sensitisers according to harmonised classification, the number increased to 17% when using other information sources. Furthermore, sensitisers were declared across several sections of the SDSs, hampering easy access of such information. In conclusion, there are inconsistencies in hazard identification of cleaning agents and their ingredients. Hence, SDSs may not altogether fulfil its hazard information role. Improved criteria for identifying sensitisers and respiratory irritants are warranted. Additionally, we argue that all ingredients should be listed in section 3 regardless of concentration, to facilitate access of information about sensitising properties. •We reviewed hazard information in 504 safety data sheets for cleaning agents.•The most frequently found hazard labels concerned corrosion and irritation.•Only 3% of products were labelled as skin sensitisers and none as asthmagens.•Identification of sensitisers differs widely between hazard information sources.